Exploring the acceptance of mixed reality technology innovation among mining industry workers - Wecka Imam Yudhistyra; Chalita Srinuan (My University, 2024)
Mixed Reality (MR) technology is an innovative technology that has the capability to transform and boost productivity in the mining industry. At the same time, the scarcity of guidelines and research in examining the acceptance of MR technology innovation in the mining sector could make the adoption of MR technology innovation unpredictable. Therefore, in order to support the successful adoption of MR technology innovation in the mining sector, this manuscript is designed to better understand the factors influencing its acceptance among workers. Based on the literature review, five factors are hypothesized to influence the acceptance of mining industry workers regarding MR technology innovation. The factors underwent testing on a sample of 253 mining industry workers, which was obtained via an office-intercept survey and processed using SmartPLS software. The model has proven to be highly robust, as indicated by its outstanding scores in validity, reliability, multicollinearity, and goodness of fit. The results from the analysis indicate that attitude, perceived usefulness, and perceived compatibility are significant factors influencing the acceptance of MR technology innovation. While perceived novelty is an important factor affecting attitude, it does not significantly impact the acceptance of MR technology innovation. Moreover, perceived ease of use was not found to be a significant factor in influencing the attitude and intention to adopt MR technology innovation. This research offers both theoretical and managerial implications for its findings.
Keywords: Technology Adoption and User Behaviour